Thermodynamic Analysis of an Integrated Hydrogen Production System Based on Solar and Nuclear Energy Sources in the UAE - Babu, Binish Sam (2013)
A Master of Science thesis in Mechanical Engineering by Binish Sam Babu entitled, "Thermodynamic Analysis of an Integrated Hydrogen Production System Based on Solar and Nuclear Energy Sources in the UAE," submitted in December 2013. Thesis advisor is Dr. Mehmet Fatih Orhan. Available are both soft and hard copies of the thesis.